Avaliação do fosfato de nióbio como catalisador heterogêneo na esterificação de ácido oleico com acetato de metila - Alves, Matheus Afonso de Lima (2017)
The concern about global warming and the search for energy security are main responsible for promote the development of renewable fuels. Among biofuels, biodiesel is a potential successor to fossil fuels because it is an environmentally better source of energy, and the search for new technologies for your production as allows the use of feedstock and byproducts efficiently and sustainable is highly encouraged. Thus, the objective of this study was to investigate the esterification reaction of oleic acid with methyl acetate catalyzed by niobium phosphate. The catalysts selected was niobium phosphate, which presented amorphous structure and high surface area by X-ray diffraction (XRD) and textural analysis using the BET method (Brunauer-Emmett-Teller). The catalytic tests were performed as planned by an experimental design and the higher levels established showed the best methyl oleate (biodiesel) concentration results. When the reaction conditions were 230°C, 10 wt% of catalyst and molar ratio of oleic acid to methyl acetate of 1:10, in 4 hours of reaction it was reached 76.88 wt% of methyl oleate concentration. The results were statistically analyzed and the studied variables were significant, with temperature being the most expressive factor, allowing the development of linear models, validating the results obtained. To optimize the production process and identify the best reaction conditions, a kinetic study of the reaction was carried out, varying the temperature, the mass percentage of the catalyst and the molar ratio. After 2 hours of reaction, it was possible to obtain the 81.52 wt% methyl oleate concentration using 240°C temperature, 10 wt% of catalyst and oleic acid/methyl acetate molar ratio of 1:10. About these conditions, the catalyst was recovered and reused without treatment in 5 reaction cycles, showing a decrease in the catalytic activity gradually over the course of the cycles. The reaction was also carried out without the presence of a catalyst, in order to observe the importance of the use of niobium phosphate, and presented a maximum concentration of 37.98 wt% of methyl oleate after 6 hours of reaction. The esterification between oleic acid and methyl acetate showed significant results for its use and the niobium phosphate can be considered a promising heterogeneous catalyst for biodiesel synthesis.